Heuristic hybrids for the quadratic assignment problem - Chua, Geoffrey Bryan Ang (2004)
This thesis explores the use of hybridized heuristic methods in solving the Quadratic Assignment Problem (QAP), a classical NP-complete combinatorial problem. Previous research works have resulted in a number of algorithm designs suitable for solving the QAP. Using these available algorithms as well as algorithms used for other problems, this thesis shows empirically that the hybridization of heuristic methods is better than non-hybridization in solving the QAP. Population-based heuristics such as Genetic Algorithms and Ant Colony Optimization are used together with local optimizers such as Simulated Annealing and Tabu Search. Furthermore, initial results show that Ant Colony Optimization hybridized with Tabu Search (ACOTS) performs significantly fastest among the hybridized algorithms considered in this thesis, particularly problem size 19.
"May 2004."
Vita.
Thesis (M.S. Applied Mathematics)--University of the Philippines, Diliman.
Keywords: Quadratic assignment problem -- Mathematics; Heuristic algorithms -- Mathematics